Distribution and Carbon Sequestration Potential of Cola Laurifolia Mast.: A Dominant Native Riparian Species Along Permanent Rivers in Sub-Saharan Africa - Kabore, Gouwidida Elice; Bayen, Philippe; Dayamba, Sizabda Djibril; Thiombiano, Adjima (European Scientific Journal, ESJ, 2022)
Species-specific models for estimating aboveground biomass (AGB) are the accurate means of quantifying speciesâ€™ carbon pools. Cola laurifolia Mast., a dominant and multi-purpose riparian species along the Mouhoun River in Burkina Faso have a regressive population. Few scientific studies exist concerning this riparian species population and carbon stock capacity. This study aims to allow this gap by formulating a species-specific allometric model for assessing with direct method for Cola laurifolia leave, branches, stem and whole AGB. Parameters used to perform models are tree diameter at breast height (DBH), basal diameter at 20 cm (D20), height (H), and mean crown diameter (CD) using data from 30 trees. Population structure shows a low regeneration potential at all of the studied river zones (i.e. upstream, intermediate and downstream zones). The carbon stock was found to be 54.14 kg C tree-1 and 9.24 Mg C. ha-1. The density of C. laurifolia was higher in downstream zone, and consequently the carbon stock was higher in these areas. The log-log linear model is the best-fitted form incorporated DBH and H as predictors. This form is best fitted for the three tree components (i.e. leaves, branches, stem) and the AGB. The AGB model is more accurate with high coefficient of determination and low RSE (RÂ²=0.92; RSE=0.28) contrasted with leaves models. The global model has the best goodness of fit because of a low relative error (-0.213 %) compared to the use of three component models. The accuracy of our species-specific model confirms the need to develop such models for greater accuracy in AGB estimations.